Reversing the Financial Accelerator : Credit Conditions and Macro-Financial Linkages - Bayoumi, Tamim; Darius, Reginald (Washington, D.C. : International Monetary Fund, 2011)
This paper examines the role of credit markets in the transmission of U.S. macro-financial shocks through the prism of a financial conditions index (FCI) based on a vector autoregression (VAR) methodology. It explores the relative predictive power of market variables compared to credit standards/conditions. The main conclusion is that under plausible specifications credit conditions dominate market variables, highlighting the importance of credit supply. The fact that direct measures of credit conditions anticipate future movements in asset prices has an extremely important implication. Most models of the credit channel see it as an amplifier of underlying changes in financial wealth. The impact of credit conditions on growth compared to other market variables implies that credit supply drives other financial variables rather than responding to them.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet